Inhaling arsenic aggravates airway hyperreactivity by upregulating PNEC-sourced 5-HT in OVA-induced allergic asthma - Xue Lu; Zhu-Xia Tan; Ya-Xin Yao; Ze-Yan Li; Yan-Yan Zhu; Qian-Qun Yang; Zhao Li; Kun Peng; Yan Wang; De-Xiang Xu (Ecotoxicology and Environmental Safety)
Increasing epidemiological evidence has proved that early-life exposure to inorganic arsenic (As) elevates the risks of childhood asthma. The present research aimed to explore susceptibility of respiratory As exposure to allergic asthma in a mouse model. BALB/c mice on postnatal day (PND) 28 were exposed to ddH2O or NaAsO2 aerosol for 4 hours daily over 5 consecutive weeks via respiratory tract. Mice were sensitized by intraperitoneal injection of ovalbumin (OVA) combined with Alum Adjuvant on PND42 and PND56. Subsequently, mice were challenged with ddH2O or 1 %OVA through a nebulizer for 3 days starting from PND63. In As-exposed mice, OVA-sensitized goblet cell hyperplasia and airway mucosal secretion did not worsen. OVA-induced inflammatory cell infiltration and upregulation of Th2 cytokines, including IL-4, IL-5, and IL-13, were not aggravated in As-exposed mice. Interestingly, airway hyperreactivity was intensified in As-exposed asthmatic mice. Mechanistically, OVA-induced elevation of 5-hydroxytryptamine (5-HT), probably secreted by pulmonary neuroendocrine cells (PNECs), was exacerbated in As-exposed mice. OVA-induced upregulation of tryptophan hydroxylase (TPH)1 and TPH2, two 5-HT synthases, was aggravated in As-exposed mouse lungs. LX1032, a specific TPH inhibitor, suppressed As-induced elevation of pulmonary 5-HT content in asthmatic mice. Moreover, LX1032 alleviated As-evoked airway hyperreactivity in asthmatic mice. These results suggest that respiratory As exposure elevates airway hyperreactivity partially through upregulating PNEC-sourced 5-HT in OVA-induced allergic asthma, which provides significant insight about the hazards of environmental As exposure.